Conceptual change in the development of visual expertise - Erno Lehtinen; Andreas Gegenfurtner; Laura Helle; Roger Säljö (Elsevier Ltd, 2022)
Changes in working life require knowledge, which is sometimes radically different from existing expertise. Learning based on existing knowledge is not sufficient. Some knowledge is difficult to learn because it is counterintuitive. Research on conceptual change has extensively studied this type of learning challenges while students are learning scientific and mathematical concepts. However, theories of conceptual change have not been widely applied in expertise research. This study re-analyses earlier studies on medical image diagnosing and explores how theories of conceptual change explain the findings. Unlike science learning, the knowledge needed for the medical diagnosis processes did not exclusively consist of one or a few well-defined scientific concepts, but rather involved a system of various types of knowledge and practical skills.